2015
DOI: 10.1021/acs.jpcc.5b02525
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer Processes on Supported Au Nanoclusters and Nanowires and Substrate Effects

Abstract: The catalytic activity of metal nanoclusters is considered to depend on their size, morphology, and substrate type. Here we address this problem by studying changes in electron transfer processes, that are important in surface chemistry, on the example of the interaction of Li ions with gold nanostructures as a function of their sizes and substrate type. The Au nanoclusters were grown on highly ordered pyrolytic graphite (HOPG) and Al 2 O 3 surfaces. In the case of Al 2 O 3 and sputtered HOPG surface, a wide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…The data presented here show a reduction in the neutral fraction with cluster size, which is identical to the behavior of Au clusters on TiO2 [44,63,64], SiO2 [49,65], Al2O3 [66] and HOPG [66,67]. This behavior is consistent with the model that ascribes the reduction in NF with Au cluster size to the edge atoms being positively charged while the center atoms are neutral [18].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The data presented here show a reduction in the neutral fraction with cluster size, which is identical to the behavior of Au clusters on TiO2 [44,63,64], SiO2 [49,65], Al2O3 [66] and HOPG [66,67]. This behavior is consistent with the model that ascribes the reduction in NF with Au cluster size to the edge atoms being positively charged while the center atoms are neutral [18].…”
Section: Discussionsupporting
confidence: 88%
“…Bonding to such π orbitals could remove charge from the edge atoms in a similar manner as for Au bonding to a substrate O atom. The NF for low energy Li + scattered from Au nanoclusters supported on HOPG show a similar decrease of the NF as a function of Au coverage [66,67], which suggests that the bonding of the edge atoms to the substrate is via π orbitals for both single layer Gr and bulk graphite surfaces.…”
Section: Discussionmentioning
confidence: 83%
“…Such a behavior has been observed in low energy alkali ion scattering from Au and Ag nanoclusters in Refs. [48,50,51], and a decrease of edge atom charge for clusters that are smaller than those considered here may be the reason. Thus, the extrapolation of the model to a cluster diameter of zero in Figs.…”
Section: Modelmentioning
confidence: 78%
“…This is because the alkali LEIS technique is adept for studying surfaces composed of multiple elements and can address questions about the charge state of those elements. Previous results have shown that the ions scattered from Au and Ag nanoclusters on an oxide and other substrates have a much higher neutralization probability than those scattered from the bulk metal, and that neutralization decreases as the cluster size increases [48][49][50][51][52][53][54][55]. Although it is possible that the alkali LEIS neutralization rate and the Au nanocluster catalytic activity are related, such a correlation has not yet been confirmed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation